Factors Related To Vaginal Discharge In Female Teenagers At SMAS Pab 6 Helvetia, Deli Serdang District - Siahaan, May Frinsiska; Sembiring, Elya Rosa Br; Damanik, Syahroni; Marlina, Marlina (Universitas Prima Indonesia, 2025)
According to the World Health Organization (WHO), every year teenagers experience sexually transmitted diseases (STDs) with symptoms of vaginal discharge increasing by 5%. Even in the United States, the occurrence of vaginal discharge in teenage girls continues to increase from year to year. The existence of this problem requires prevention. While European women in 2013 as many as 739,004,470 people and experienced vaginal discharge by 25%. The problem behind this study is the occurrence of vaginal discharge which is often complained of by teenage girls. Factors suspected of being related to vaginal discharge are personal hygiene, stress, and the use of vaginal cleansers. Purpose: This study aims to determine the factors related to vaginal discharge in teenage girls. Method: This study is an analytical survey study (explanatory research) with a cross-sectional approach. The study was conducted at SMAS PAB 6 HELVETIA. The study population was 32 teenage girls, and all of them were used as samples (total sampling). The data were analyzed using the Chi-Square test at a 95% confidence level ( = 0.05). Results: Based on the results of the study, it was shown that the factors related to vaginal discharge in female adolescents at SMAS PAB 6 HELVETIA were personal hygiene with a fairly strong correlation (p = 0.006); stress with a fairly strong correlation (p = 0.018); use of vaginal cleansers with a fairly strong correlation (p = 0.006). The occurrence of vaginal discharge in adolescent girls is influenced by personal hygiene, stress, and the use of vaginal cleansers. SMAS PAB 6 HELVETIA Medan can provide appropriate education about personal hygiene to female students, prevent stress, and the proper use of vaginal cleansers.